Compressive Strength of New Glass Ionomer Cement Technology based Restorative Materials after Thermocycling and Cyclic Loading - Valentina Brzović Rajić; Ana Ivanišević Malčić; Zeynep Bilge Kütük; Sevil Gurgan; Silvana Jukić Krmek; Ivana Miletić (University of Zagreb. School of Dental Medicine, 2019)
Objective: The objective of the study was to compare compressive strengths of two glass ionomerbased materials, with and without a light-cured, nano-filled coating, after cyclic loading and thermocycling. Materials and methods: To determine compressive strength of new restorative materials over a longer period of time, materials were analysed under simulated conditions where cyclic loading replicated masticatory loading and thermocycling simulated thermal oscillations in the oral cavity. Four groups of samples (n=7)-(1) Equia Fil (GC, Tokyo, Japan) uncoated; (2) Equia Fil coated with Equia Coat (GC, Tokyo, Japan); (3) Equia Forte Fil (GC, Tokyo, Japan) uncoated; and (4) Equia Forte Fil coated with Equia Forte coat (GC, Tokyo, Japan)-were subjected to cyclic loading (240,000 cycles) using a chewing simulator (MOD, Esetron Smart Robotechnologies, Ankara, Turkey). Results: Compressive strength measurements were performed according to ISO 9917-1:2007, using the universal mechanical testing machine (Instron, Lloyd, UK). Scanning electron microscope (SEM) analysis was performed after thermocycling. There were no statistically significant differences between Equia Fil and Equia Forte Fil irrespective of the coating (p<0.05), but a trend of increasing compressive strength in the coated samples was observed. Conclusions: Coating increases the compressive strength of Equia Fil and Equia Forte Fil, but not significantly.